POLITIK ISLAM DALAM PUSARAN SEJARAH SURAKARTA - Hermanu Joebagio (Millah: Journal of Religious Studies, 2013)
This article tries to analysis political strategy at the time of islamzation in 16th to 19th century. This analysis use political theory, it’s descending and ascending of power. By supporting of the Saints, it’s possible for Jin Bun (Raden Patah) built the Kingdom of Demak, and by supporting not only spread of islamization, but also reinforced political and social structure. Implication of that Islam was possible running embraces in Demak society. Conversion from Hindu to Islam could be investigation by language symbolism, for instance, the title of Ngabdurrahman Sayidin Panatagama Khalifatullah. Although the Kingdom of Demak had been collapsed, but islamization processes moved to Pajang and than to the Palace of Mataram. Furthermore Sultanate of Mataram, Sultan Agung, introduceda new strategy for spread of islamization in Java, that were: (1) palace as center ofIslamization, and (2) Islam center points of Javanese culture. The new strategy were continued of political strategy of the Saints. In the other side, Sultan Agung  supported the Saints to built pesantren or madrasah (local boarding school) that had been a grassroots political legitimation. And a grassroot power based on values of solidarity or ashabiyyah.